Socio-Demographic, Clinical and Laboratory Profile of Leptospirosis Cases Registered At SMIMER, Surat - Parmar, Gaurang; Kava, Dilip; Mehta, Shreyash; Mallick, Kallol; Prasad, Rachana; Bansal, RK; Rupani, Mihir (National Journal of Community Medicine, 2013)
Context: Leptospirosis is a zoonotic disease with worldwide distribution caused by pathogenic leptospira. Leptospirosis is more prevalent in South Gujarat due to heavy rain fall and clay soil structure. The current study was conducted to analyse the profile of patients with Leptospirosis admitted in Surat Municipal Institute of Medical Education and Research (SMIMER), Surat. Methods and Material: This prospective study, involves patients visiting SMIMER hospital during the time period of 1st August to 31st October 2011 who were suspected for Leptospirosis. Their presenting complaints, examination findings, lab findings, treatment and outcome were recorded and analyzed based on the modified Faine’s criteria. Results: Among the 24 suspected cases of Leptospirosis, 14 (59%) were males and age of patients ranged from 10 to 65 years with mean age of 34 years. Fever, myalgia, and headache were predominant complaints and all had history of contact with animals or contaminated environment. Liver functions and renal functions were deranged in 96% and 63% cases respectively. Fifteen patients were found positive for Leptospirosis. Fifteen (63%) patients had Weil’s syndrome and 8 had ARDS. There were 4 deaths, all were males, had ARF and presented with systolic hypotension. Conclusions: The disease prevalence usually increases during rainy season. Most cases were from rural origin and all had history of contact with animals. Myalgia (calf tenderness), jaundice and conjunctival suffusion were characteristic physical examination findings. Jaundice and renal failure are associated with severity of the disease and are considered bad prognostic signs with high mortality rate (16%).